2021
DOI: 10.14238/sp23.4.2021.235-41
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Asap Rokok terhadap Derajat Keparahan Pneumonia Anak Usia di Bawah 5 Tahun

Abstract: Latar belakang. Pneumonia merupakan penyebab utama kematian pada anak usia di bawah 5 tahun di dunia. Di Indonesia, prevalensi pneumonia pada anak di bawah usia 5 tahun mencapai 18,5 per mil. Paparan asap rokok merupakan salah satu faktor risiko pneumonia. Tujuan. Membuktikan hubungan paparan asap rokok terhadap pneumonia berat pada anak usia di bawah 5 tahun.Metode. Penelitian ini merupakan studi kasus kontrol di Rumah Sakit Atma Jaya. Kelompok kasus didefinisikan sebagai anak usia di bawah 5 tahun dengan pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results of this study indicate that there is no relationship between basic immunization status and the severity of pneumonia. These findings are consistent with research conducted by Albuhairi et al (2021) and Stefani (2021), who also found no association between basic immunization status and pneumonia severity in children under five 10,11 .…”
Section: Basic Immunization Status and Severity Of Pneumonia In Child...supporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study indicate that there is no relationship between basic immunization status and the severity of pneumonia. These findings are consistent with research conducted by Albuhairi et al (2021) and Stefani (2021), who also found no association between basic immunization status and pneumonia severity in children under five 10,11 .…”
Section: Basic Immunization Status and Severity Of Pneumonia In Child...supporting
confidence: 92%
“…Similar results were found in a study conducted in Vietnam, which reported that exposure to cigarette smoke increases the risk of severe pneumonia in children fourfold compared to those not exposed. Stefani (2021) also found that family smoking behavior is a significant factor in the severity of pneumonia in children 11 .…”
Section: Exposure To Cigarette Smoke and Severity Of Pneumonia In Chi...mentioning
confidence: 98%